The association between phenotypes of polycystic ovary syndrome and metabolic dysfunction-associated fatty liver disease - So-hyeon Hong; Yeon-Ah Sung; Young Sun Hong; Do Kyeong Song; Hyein Jung; Kyungah Jeong; Hyewon Chung; Hyejin Lee (Frontiers in Endocrinology, 2025)
IntroductionPolycystic ovary syndrome (PCOS) is associated with an increased risk of non-alcoholic fatty liver disease (NAFLD). With the introduction of the new definition of metabolic dysfunction-associated fatty liver disease (MAFLD), there has been a lack of studies investigating the prevalence and clinical characteristics of PCOS and its phenotypes, including hyperandrogenism (HA), oligoanovulation (OA), and polycystic ovarian morphology (PCO) in association with MAFLD. The aim of this study is to explore MAFLD prevalence in young women with PCOS and determine the independent impact of PCOS phenotypes on MAFLD.MethodsThis cross-sectional study included 1,422 women with PCOS diagnosed using the Rotterdam criteria, the presence of at least two of three diagnostic criteria: 1) hyperandrogenism (HA), 2) oligoanovulation (OA), and 3) polycystic ovary morphology (PCO).ResultsAmong women with PCOS, 31.2% had NAFLD, and 65.1% of them were diagnosed with MAFLD. In PCOS phenotypes, MAFLD prevalence was 25.1% for HA+OA+PCO, 27.6% for HA+OA, 8.8% for HA+PCO, and 13.0% for OA+PCO. Women with PCOS and HA+OA+PCO had higher odds of MAFLD (OR [95% CI] of 1.47 [1.04–2.09]), as did those with HA+OA (1.87 [1.18–2.96]), after adjusting for demographic and clinical factors. However, the association between women with PCOS and HA+PCO and MAFLD was not statistically significant (0.51 [0.21–1.24]).DiscussionIn women with PCOS, both HA+OA+PCO and HA+OA phenotypes were independently associated with MAFLD. HA and OA may contribute independently to the higher prevalence of MAFLD in these individuals.